Industry Participation in the Academic Development (Homoeopathy for All, 2022)
Awareness of homoeopathy  increased after COVID. It is felt  across the levels of the homoeopathic  supply chain from the doctors,  retailers, distributors, whole-sellers  and manufacturers. In this scenario,  industry-academia collaborations  will help the whole homoeopathic  field for better-trained homoeopaths,  better quality products, a better  educational environment, and better  industrial growth. This article helps  understand the ways and means  of academic development through  industry participation from our own  experience at Schwabe India.
Keywords: homoeopathy; environment; experience